DESIGN OF ARTIFICIAL NEURAL NETWORK SOFTWARE FOR PREDICTING THE HEALTH GRADE IN A TELEPHONE EXCHANGE - Wiratmoko Yuwono; Yodik Iwan Herlambang; Mauridhi Hery Purnomo; Prima Kristalina (SAINTEKBU, 2008)
Application of artificial neural network software ( ANN ) has been implemented forpredicting many thing and replace the conventional ways of predicting method using linearregression. Back Propagation algorithm can be used to reach the result of the program thatcan predict the telephone exchange health grade according to the data that has beenrecorded before. By predicting each parameter that has correlation to the telephoneexchange health grade, we can predict the telephone exchange health grade in the nextperiod.Kata kunci : jaringan syaraf tiruan, propagasi balik, nilai kesehatan sentral.